Mobile Application Design for Smart Tourism with Augmented Reality Using User-Centered Design Method - Elika Thea Kirana (STMIK Banjarbaru, 2024)
AbstractIndonesia has many beautiful and attractive tourist destinations. However, limited information about these locations has made tourists less interested in exploring the cities. Traditional methods of providing information about tourist sites, such as print media, have proven to be less effective in providing information. To address this issue, it is necessary to utilize information technology. One way to do this is by designing a tourism app with Augmented Reality (AR) using the User-Centered Design (UCD) method. UCD is a method that involves the user in every step of the process. Users will be involved in every process, from the design of the application to the final product. Users will be given a questionnaire related to the design until it gets the required interface design. In this study, an average score of 4.16 was obtained, which show the application design can provide complete travel information of user needs.Keywords: Tourism; Indonesia; User-Centered Design; Interface Design; Augmented Reality Application AbstrakIndonesia mempunyai wisata yang indah dan menarik, namun karena terbatasnya informasi, wisatawan menjadi kurang tertarik untuk mengetahui apa saja yang ada di kota tersebut. Penyampaian informasi mengenai lokasi wisata dengan menggunakan media cetak, brosur dan spanduk di tempat wisata kurang efektif dalam memberikan informasi. Karena kemajuan teknologi sudah sangat pesat, maka diperlukan suatu cara untuk memanfaatkan teknologi informasi. Melalui perancangan aplikasi pariwisata dengan Augmented Reality (AR) menggunakan metode User-Centered Design (UCD). UCD adalah metode yang melibatkan pengguna dalam setiap langkah proses. Dari perancangan aplikasi yang dibuat, pengguna akan terus terlibat dalam setiap prosesnya. Pengguna akan diberikan kuisioner terkait perancangan, jika perancangan belum sempurna, proses UCD akan diulangi hingga mendapatkan desain antarmuka yang dibutuhkan sehingga dapat memenuhi kebutuhan informasi lokasi pengguna. Dari penelitian ini, didapatkanlah rata-rata skor 4.16 yang menunjukan rancangan aplikasi ini dapat dengan mudah digunakan oleh pengguna.Kata Kunci: Pariwisata; Indonesia; User Centered Design; Augmented Reality Application